Answer:
1 a) [tex]-7g+4g+2[/tex]
1 b) [tex]-3g+2[/tex]
2 a) [tex]2\lambda-4-6\lambda[/tex]
2 b) [tex]-4\lambda-4[/tex]
Step-by-step explanation:
Given statements:
1. Find the sum of -7g and 4g + 2
2. Find the difference when 6[tex]\lambda[/tex] is subtracted from 2[tex]\lambda[/tex] - 4
a) To write an expression based on the given statement
b) To simplify the expression
Solution:
1) The expression for sum of [tex]-7g[/tex] and [tex]4g+2[/tex] is given as:
1 a) [tex]-7g+4g+2[/tex]
The above expression can be simplified by combining the like terms:
1 b) ⇒ [tex]-3g+2[/tex] [ As [tex]-7g+4g=-3g[/tex] ]
2) The expression for the difference when [tex]6\lambda[/tex] is subtracted from [tex]2\lambda-4[/tex] can be given as:
2 a) [tex]2\lambda-4-6\lambda[/tex]
The above expression can be simplified by combining the like terms:
2 b) ⇒ [tex]-4\lambda-4[/tex] [ As [tex]2\lambda-6\lambda = -4\lambda[/tex] ]